Influence of electronic word of mouth on purchase intention of fashion products in social networking websites - Anum Saleem; Abida Ellahi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The growth of social networking sites has changed the living style of people around the globe and it has also become an important tool for marketers. This growth has also emerged electronic word of mouth that significantly shapes the purchase intention of consumers. This study investigates the outcome of electronic word of mouth on purchase intention of Facebook users. It also identifies the major factors influencing the electronic word of mouth to buy fashion products. A survey was conducted to collect data from 503 Facebook users. Data collected through questionnaire was empirically analyzed using SPSS Process macro developed by Hayes and Preacher (2014). The findings confirm the electronic word of mouth is an effective factor influencing purchase intention of fashion brands. The findings also confirm the role of homophily, trustworthiness, expertness, informational influence and high fashion involvement as major factors influencing electronic word of mouth. Findings from the study help to assist the companies that use social networking sites like Facebook for promotion of their products in targeting the factors that have major influence on purchase intention of fashion products.
Keywords: 330; electronic word of mouth; purchase intention; homophily; expertness; trustworthiness; informational influence; high fashion involvement; Facebook usage intensity